Aerogel insulation pipe and preparation method thereof
By using cement and other cementitious materials and aerogel powder in pipeline insulation and using 3D printing technology to form, the problems of uneven dispersion and deformation of aerogels in pipeline insulation are solved, and excellent insulation effect and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411729881.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, when aerogel is used for pipeline insulation, the coating obtained by coating preparation is thinner and cannot fully utilize the advantages of insulation, or the aerogel fiber felt is bent and pasted, but the bending process will cause the fiber felt to deform, affecting the use effect.
Cement, fly ash, limestone powder and tackifying active powder are used as gelling materials, aerogel powder is added as insulation filler, and the block material is formed by 3D printing, cut into suitable sizes for socketing to industrial thermal pipelines.
The uniform dispersion and full utilization of aerogels in pipeline insulation is achieved, the insulation effect and mechanical properties are improved, and the problems of light aggregate floating and crushing in cement slurry are overcome.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based building materials, and in particular to an aerogel thermal insulation pipe and a preparation method thereof. Background Art
[0002] Industrial pipelines often require insulation and cooling measures. Currently, rock wool, polyurethane foam and other materials are commonly used as insulation materials. However, the heat resistance and durability of the above materials are poor and they often need to be replaced.
[0003] Aerogel is a thermal insulation material developed in recent years. It has light weight and low thermal conductivity and is widely used in the field of thermal insulation. However, aerogel insulation materials are usually used as aerogel fiber felts, and the aerogel is reinforced with fibers.
[0004] Prior art CN106007635A discloses an aerogel composite material with a dust-free surface treatment, which uses aerogel felt, aerogel plate, aerogel cylinder and aerogel special-shaped parts as substrates, and a dense coating is applied on the surface of the substrate. CN106630930A discloses a method for continuously preparing aerogel thermal insulation felt, which activates the groups on the surface of mineral fibers, cross-links and gels with hydrophilic polymer materials, so that the surface of the mineral fibers forms a gel so that it has flexibility, and further forms a composite gel after being uniformly compounded with silicon dioxide wet gel, and the composite gel is continuously formed and step-dried to obtain a roll. CN111646769A discloses a construction method for a gas steam boiler flue gas duct, including the following steps: S1 steel structure layer construction: according to the design drawings, mark the installation position of the flue gas duct column, and build the steel frame on the marked column position; S2 use mesh cloth to wrap the inside and outside of the steel structure layer into a circle, forming a hollow double-layer mesh cloth semi-enclosed structure; S3 fill the hollow double-layer mesh cloth semi-enclosed structure with insulation layer fluid, and remove the mesh cloth after natural solidification; S4 spray the silane coupling agent and acrylic resin in the airtight layer on the surface of the insulation layer in sequence. However, when aerogel is used for pipeline insulation, aerogel is often used as a filler to prepare coatings. The coating prepared by the coating is thin and cannot give full play to the insulation advantage, or the aerogel fiber felt is bent and then pasted, but the bending process will cause the fiber felt to deform, affecting the use effect. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides an aerogel insulation pipe, which adopts cement, fly ash, limestone powder and thickening active powder as gelling material, adds aerogel powder as insulation filler, and adds water reducer, alcohol amine, gas-phase nano-silicon dioxide, polyvinyl alcohol, early strength agent and defoaming agent as additives. The block material is formed by 3D printing, and the inner diameter and outer diameter are cut according to the pipe size, which is convenient for sleeve connection on industrial thermal pipes, and has excellent insulation effect and mechanical properties.
[0006] Specifically, the aerogel insulation pipe of the present invention is prepared by mixing, 3D printing and cutting the following raw materials in parts by weight:
[0007] 100-110 parts of cement, 20-30 parts of fly ash, 10-20 parts of limestone powder, 20-30 parts of thickening active powder, 8-12 parts of aerogel powder, 2-3 parts of water reducer, 1-2 parts of amine, 1-2 parts of fumed nano-silica, 0.5-0.8 parts of polyethylene glycol, 0.3-0.5 parts of early strength agent, 0.2-0.3 parts of defoaming agent, and 45-50 parts of water.
[0008] Aerogel has good thermal insulation performance, but its density is much smaller than that of lightweight aggregates such as ceramsite, expanded perlite, and expanded vermiculite. It is very easy to float in cement slurry, difficult to disperse evenly, and easy to break during forced stirring. Therefore, the present invention uses 3D printing technology for molding and uses aerogel powder as a lightweight filler to overcome the technical difficulties caused by subsequent mixing, cutting and other processes caused by lightweight aggregates. By adjusting the viscosity of cement slurry, the aerogel powder is evenly dispersed in the cement slurry, thereby improving the molding effect.
[0009] Preferably, the preparation process of the viscosity-enhancing active powder is: graphite tailings, magnesium slag, and rice husk ash are uniformly mixed in a mass ratio of 1: (0.6-0.8): (0.2-0.3), calcined at high temperature, rapidly cooled, and ground to obtain the active powder.
[0010] In order to meet the needs of 3D printing, the cement slurry needs to have a certain viscosity and plasticity. In order to meet the needs of subsequent cutting and processing, the molded body needs to have certain mechanical properties. The present invention uses cement as the main cementitious material, adds fly ash, limestone powder and thickening active powder as cementitious materials, and cement hydration forms CSH gel and calcium aluminate to form a basic bonding skeleton. Fly ash has a volcanic ash effect and can react with calcium hydroxide produced by cement hydration to generate hydration products to supplement cement hydration. Limestone powder can increase the viscosity and plasticity of cement slurry, and can play a micro-aggregate effect to improve the compaction performance.
[0011] Powdered graphite tailings are produced during graphite mining, and its main chemical composition is SiO 2 、Al 2 O 3 ,CaO,Fe 2 O 3 Among them, SiO 2 The largest proportion, magnesium slag is the industrial waste slag produced in the process of magnesium smelting, the main chemical components are CaO, SiO 2 ,MgO,Fe 2 O 3, and contains some f-CaO. Rice husk ash is the powder produced after burning rice husk, and its main component is SiO 2 , and contains a certain amount of C, K, Na and other elements. Graphite tailings have low activity, magnesium slag has high alkalinity, and rice husk ash has a high silicon content and has a certain activity. The present invention has obtained a new admixture by a large number of experimental studies, calcining the three at high temperature, then rapidly cooling and grinding. During the test, it was found that it contains a large amount of C 3 S.C. 2 S, and contains some C 3 A and CaO-MgO-SiO 2 The solid solution not only greatly improves the strength, but also has a higher water demand, which can increase the viscosity of the slurry. The use of the gelling material of the present invention can offset the loss of mechanical strength caused by the addition of aerogel powder, so that the molded body has higher strength, which is beneficial to 3D printing and subsequent cutting processes.
[0012] Preferably, the cement is at least one of ordinary Portland cement and Portland cement.
[0013] Preferably, the fly ash is primary fly ash or secondary fly ash.
[0014] Preferably, the particle size of the limestone powder is ≤45 μm.
[0015] Preferably, the aerogel powder has a particle size of 10-25 μm.
[0016] Preferably, the water reducer is a polycarboxylate water reducer.
[0017] Preferably, the alcoholamine is at least one of triethanolamine, triisopropanolamine and diethanolamine.
[0018] Preferably, the early strength agent is at least one of calcium nitrate and calcium chloride.
[0019] Preferably, the defoamer is a silicone defoamer.
[0020] Preferably, in the preparation process of the viscosity-increasing active powder, the high-temperature calcination is calcination at 1200-1300° C. for 2-4 hours, and the powder is ground to a particle size of ≤75 μm.
[0021] The invention adds gas-phase nano-silicon dioxide, which releases heat during its dissolution in water, can increase the viscosity of the slurry, and improve the mechanical properties of cement-based materials, with the effect being completely better than that of nano-silicon dioxide. The addition of polyethylene glycol can improve the dispersibility of aerogel powder, the water reducer can improve the workability of the slurry, and the alcohol amine and the early strength agent can improve the early and late mechanical properties of cement-based materials.
[0022] The present invention also relates to a method for preparing the above-mentioned aerogel insulation pipe, which specifically comprises the following steps:
[0023] 1) Weigh each raw material by weight,
[0024] 2) Mix all the raw materials evenly to obtain 3D printing slurry.
[0025] 3) Print the 3D printing slurry into shape to obtain a blank.
[0026] 4) Curing the green body,
[0027] 5) Cut to size.
[0028] Preferably, step 2) can be carried out by mixing in steps to mix the raw materials evenly.
[0029] Preferably, step 4) adopts standard curing.
[0030] Preferably, in step 5), the inner diameter of the cutting can be determined according to the size of the industrial pipeline, and the outer diameter of the cutting can be determined according to the insulation effect and thickness requirements. The aerogel insulation pipe obtained by cutting can be plugged into and socketed with the industrial pipeline.
[0031] The present invention has the following technical advantages:
[0032] 1. The present invention uses graphite tailings, coal slag and rice husk ash to prepare thickening active powder, which has good thickening effect and hydration activity, and together with limestone powder and fumed nano-silicon dioxide, it increases the viscosity of the slurry and ensures 3D printing molding.
[0033] 2. The present invention uses cement, fly ash, limestone powder, and thickening active powder as gelling materials, and adds alcohol amine and early strength agent to ensure the mechanical properties of the molded body and provide strength guarantee for the cutting process.
[0034] 3. The present invention utilizes 3D printing to prepare the blank, and after curing, the blank is cut according to size to prepare the aerogel insulation pipe, which has good insulation effect, excellent mechanical properties, and designable size. DETAILED DESCRIPTION
[0035] In order to prove the technical effect of the present invention, 3D printing was used to prepare the aerogel thermal insulation material blank, and the mechanical properties and thermal insulation performance tests were carried out after standard curing for 28 days. At the same time, the molded body was cut to observe its machinability. During the test, the cement used P·O42.5 cement, the fly ash used secondary fly ash, the limestone powder particle size was ≤45μm, the aerogel powder used silica aerogel powder with a particle size of 10-25μm, the water reducer used polycarboxylic acid water reducer, and the defoamer used silicone defoamer.
[0036] Example 1, aerogel thermal insulation material, composed of the following raw materials in parts by weight: 110 parts of cement, 25 parts of fly ash, 18 parts of limestone powder, 23 parts of viscosity-enhancing active powder, 10 parts of aerogel powder, 3 parts of water reducer, 2 parts of triethanolamine, 1.5 parts of fumed nano-silicon dioxide, 0.6 parts of polyethylene glycol, 0.4 parts of calcium nitrate, 0.2 parts of defoaming agent, 49 parts of water,
[0037] The preparation process of the viscosity-enhancing active powder is as follows: graphite tailings, magnesium slag and rice husk ash are uniformly mixed in a mass ratio of 1:0.7:0.2, calcined at 1280° C. for 3 hours, rapidly cooled, and ground to a particle size of ≤75 μm.
[0038] After testing, the slurry 3D printing effect is good, without collapse, 28d compressive strength of 4.6MPa, thermal conductivity of 0.054W / (m·K), no slag falling off during cutting, no breakage, and good machinability.
[0039] Example 2, aerogel thermal insulation material, composed of the following raw materials in parts by weight: 100 parts of cement, 30 parts of fly ash, 15 parts of limestone powder, 30 parts of viscosity-enhancing active powder, 12 parts of aerogel powder, 2.5 parts of water reducer, 2 parts of triethanolamine, 2 parts of fumed nano-silicon dioxide, 0.7 parts of polyethylene glycol, 0.3 parts of calcium nitrate, 0.3 parts of defoaming agent, 49 parts of water,
[0040] The preparation process of the viscosity-enhancing active powder is as follows: graphite tailings, magnesium slag and rice husk ash are uniformly mixed in a mass ratio of 1:0.8:0.2, calcined at 1280° C. for 3 hours, rapidly cooled, and ground to a particle size of ≤75 μm.
[0041] After testing, the slurry 3D printing effect is good, without collapse, 28d compressive strength is 4.9MPa, thermal conductivity is 0.050W / (m·K), there is no slag or breakage during the cutting process, and the processability is good.
[0042] Comparative Example 1
[0043] The aerogel thermal insulation material is composed of the following raw materials in parts by weight: 110 parts of cement, 25 parts of fly ash, 18 parts of limestone powder, 23 parts of silica fume, 10 parts of aerogel powder, 3 parts of water reducer, 2 parts of triethanolamine, 1.5 parts of fumed nano-silicon dioxide, 0.6 parts of polyethylene glycol, 0.4 parts of calcium nitrate, 0.2 parts of defoaming agent, and 49 parts of water.
[0044] After testing, it was found that the slurry 3D printing collapsed and could only be formed by mold. The molded specimen had a 28d compressive strength of 1.3MPa and a thermal conductivity of 0.093W / (m·K). The cutting process caused slag and corner loss.
[0045] Comparative Example 2
[0046] Aerogel thermal insulation material is composed of the following raw materials in parts by weight: 110 parts of cement, 25 parts of fly ash, 18 parts of mineral powder, 23 parts of viscosity-enhancing active powder, 10 parts of aerogel powder, 3 parts of water reducer, 2 parts of triethanolamine, 1.5 parts of fumed nano-silicon dioxide, 0.6 parts of polyethylene glycol, 0.4 parts of calcium nitrate, 0.2 parts of defoaming agent, and 49 parts of water.
[0047] The preparation process of the viscosity-enhancing active powder is as follows: graphite tailings and rice husk ash are uniformly mixed in a mass ratio of 1:0.9, calcined at 1280° C. for 3 hours, rapidly cooled, and ground to a particle size of ≤75 μm.
[0048] After testing, the slurry 3D printing collapsed and had floating slurry. The compressive strength of the mold was 1.9MPa after 28 days, and the thermal conductivity was 0.080W / (m·K). The cutting process caused slag and fragmentation.
[0049] Comparative Example 3
[0050] Aerogel thermal insulation material is composed of the following raw materials in parts by weight: 110 parts of cement, 25 parts of fly ash, 18 parts of limestone powder, 23 parts of viscosity-enhancing active powder, 10 parts of aerogel powder, 3 parts of water reducer, 2 parts of triethanolamine, 1.5 parts of fumed nano-silicon dioxide, 0.6 parts of polyethylene glycol, 0.4 parts of calcium nitrate, 0.2 parts of defoaming agent, and 49 parts of water.
[0051] The preparation process of the viscosity-enhancing active powder is as follows: coal gangue, carbide slag and silica fume are uniformly mixed in a mass ratio of 1:0.7:0.2, calcined at 1280° C. for 3 hours, rapidly cooled, and ground to a particle size of ≤75 μm.
[0052] After testing, the slurry 3D printing effect is general, basically no collapse, 28d compressive strength is 2.1MPa, thermal conductivity is 0.077W / (m·K), and there is no slag and corner loss during the cutting process.
[0053] Comparative Example 4
[0054] Aerogel thermal insulation material is composed of the following raw materials in parts by weight: 110 parts of cement, 25 parts of fly ash, 18 parts of limestone powder, 23 parts of thickening active powder, 10 parts of aerogel powder, 3 parts of water reducer, 2 parts of triethanolamine, 1.5 parts of nano silicon dioxide, 0.6 parts of hydroxypropyl methyl cellulose ether, 0.4 parts of calcium nitrate, 0.2 parts of defoamer, 49 parts of water,
[0055] The preparation process of the viscosity-enhancing active powder is as follows: graphite tailings, magnesium slag and rice husk ash are uniformly mixed in a mass ratio of 1:0.7:0.2, calcined at 1280° C. for 3 hours, rapidly cooled, and ground to a particle size of ≤75 μm.
[0056] After testing, the slurry 3D printing effect is general, with slight deformation, 28d compressive strength of 2.3MPa, thermal conductivity of 0.071W / (m·K), and slag and corner loss during cutting.
[0057] Comparative Example 5
[0058] The aerogel thermal insulation material is composed of the following raw materials in parts by weight: 110 parts of 42.5 grade sulphoaluminate cement, 25 parts of fly ash, 18 parts of mineral powder, 23 parts of silica fume, 10 parts of aerogel powder, 3 parts of water reducer, 2 parts of triethanolamine, 1.5 parts of hydroxypropyl methylcellulose ether, 0.6 parts of polyvinyl alcohol, 0.4 parts of calcium nitrate, 0.2 parts of defoaming agent and 49 parts of water.
[0059] After testing, it was found that the slurry could not be 3D printed and was compacted. The compressive strength of the mold after 28 days was 0.9MPa, the thermal conductivity was 0.258W / (m·K), and it broke when cut.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An aerogel insulation pipe, characterized in that: It is prepared by mixing, 3D printing and cutting the following raw materials in parts by weight: 100-110 parts of cement, 20-30 parts of fly ash, 10-20 parts of limestone powder, 20-30 parts of thickening active powder, 8-12 parts of aerogel powder, 2-3 parts of water reducer, 1-2 parts of alcohol amine, 1-2 parts of fumed nano-silica, 0.5-0.8 parts of polyethylene glycol, 0.3-0.5 parts of early strength agent, 0.2-0.3 parts of defoamer, 45-50 parts of water, The preparation process of the viscosity-enhancing active powder is as follows: graphite tailings, magnesium slag and rice husk ash are uniformly mixed in a mass ratio of 1: (0.6-0.8): (0.2-0.3), calcined at high temperature, rapidly cooled and ground to obtain the active powder. The aerogel powder particle size is 10-25 μm; High temperature calcination is calcination at 1200-1300°C for 2-4 hours, and grinding to a particle size of ≤75μm.
2. The aerogel insulated pipe according to claim 1, characterized in that: The cement is at least one of ordinary Portland cement and Portland cement.
3. The aerogel insulated pipe according to claim 1, characterized in that: The fly ash is primary fly ash or secondary fly ash.
4. The aerogel insulated pipe according to claim 1, characterized in that: The particle size of the limestone powder is ≤45 μm.
5. The aerogel insulated pipe according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
6. The aerogel insulated pipe according to claim 1, characterized in that: The alcohol amine is at least one of triethanolamine, triisopropanolamine and diethanolamine.
7. The aerogel insulated pipe according to claim 1, characterized in that: The early strength agent is at least one of calcium nitrate and calcium chloride.
8. The method for preparing an aerogel thermal insulation pipe according to any one of claims 1 to 7, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Mix all the raw materials evenly to obtain 3D printing slurry. 3) Print the 3D printing slurry into shape to obtain a blank. 4) Curing the green body, 5) Cut to size.
Citation Information
Patent Citations
Aerogel composite material with surface subjected to dust-free treatment and preparation method
CN106007635A
Method for continuously preparing aerogel heat-insulating felt
CN106630930A
Levigated rice hull ash based composite admixture and application thereof
CN110041002A
3D printing thermal insulation concrete containing SiO2 aerogel and preparation method of 3D printing thermal insulation concrete
CN113372072A
Nano thermal insulation coating, preparation method and preparation equipment thereof
CN113563039A